The Spec UI framework - Fabry, Johan; Ducasse, Stephane; Open Textbook Library (Open Textbook Library, 2017)
Spec is the default UI framework for Pharo. To build UI's in Spec existing widgets or even complete UI's are reused and configured to form a new UI. This book first shows the basics of Spec and how it enables reuse of UIs. It then treats UI layout in detail before moving on to explaining the management of windows. Some of the more advanced widgets are also discussed as well as the dynamic features of Spec. Lastly, the book also contains a chapter with tips and tricks.
Illustrations1 Introduction2 First Contact With Examples -- 2.1 A customer satisfaction UI -- 2.2 Fun with Lists -- 2.3 Conclusion -- 3 Reusing and composing elements -- 3.1 First requirements -- 3.2 Creating a basic UI to be reused as a widget -- 3.3 Combining two basic widgets into a reusable UI -- 3.4 Managing three widgets and their interactions -- 3.5 Changing the layout of a reused widget -- 3.6 Considerations about a public configuration API -- 3.7 Conclusion -- 4 The fundamentals of Spec -- 4.1 User interface building: a composition -- 4.2 The initializeWidgets method -- 4.3 Defining UI Layouts -- 4.4 The initializePresenter method -- 4.5 Conclusion -- 5 Layout Construction -- 5.1 About layouts -- 5.2 Row and column layouts -- 5.3 Combining rows and columns -- 5.4 Setting row and column size -- 5.5 Layouts without rows or columns -- 5.6 Conclusion -- 6 Managing windows -- 6.1 Opening a window or a dialog box -- 6.2 Modal windows and the closing of windows -- 6.3 Window size and decoration -- 6.4 The final details: title, icon and about text -- 6.5 Conclusion -- 7 Advanced Widgets -- 7.1 TextModel -- 7.2 RadioButtonModel -- 7.3 TabModel -- 7.4 Toolbars and Pop-up Menus -- 7.5 Conclusion -- 8 Dynamic Spec -- 8.1 Dynamically changing an already opened UI -- 8.2 Dynamically populating a UI with widgets -- 8.3 Hacking together a UI in the Playground -- 8.4 Conclusion -- 9 Tips and Tricks -- 9.1 Integrating the different UI frameworks -- 9.2 Lists, trees and tables -- 9.3 Using the underlying widget library -- 9.4 Testing the functionality of a Spec UI
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks